Development of force measurement system of bobsled for practice of push-off phase - Lee, S.; Kim, T.; Lee, S.; Kil, S.; Hong, S. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2015)
A force measurement system for the push bar and handle of a bobsled was developed to analyse the forces exerted by members of a two-person bobsled crew. The developed system comprised eight load cells, an encoder, four cameras, and a data acquisition device and was installed on a test sled. Two load cells were installed in each of the brakeman`s push handle and the driver`s side push bar, and two load cells were located on each of the right and left ends of the push bar. The operator could adjust the sampling rate of each load cell from 50 to 200 samples/s. The motion of the crew member was recorded with the four cameras. The sled speed was recorded along with the force data. For convenient monitoring and analysis of the measured data, the four camera images were merged into a single video image, and the force data were plotted on this merged image. This image contained all of the measured data and was transmitted wirelessly to a monitor at a remote site in real time. The data measurement software was developed using LabVIEW, and the force and speed of the sled were recorded as a technical data management streaming file. The images were recorded as Audio Video Interleaved files. The technical data management streaming file was automatically converted into an Excel file when the measurement stopped. The vector components of the forces exerted by crew members were measured using this system. The data were used to analyse the exerted force with the aim of increasing the starting speed of the Korean bobsled crew.